Molecular and Immunological Methods to Confirm Toxiginicity (Microcystin Production) of Westiellopsis Prolifica Isolated from Tigris River – Iraq - Abed et al. (مجلة بغداد للعلوم)
Several toxigenic cyanobacteria produce the cyanotoxin (microcystin). Being a health and environmental hazard, screening of water sources for the presence of microcystin is increasingly becoming a recommended environmental procedure in many countries of the world. This study was conducted to assess the ability of freshwater cyanobacterial species Westiellopsis prolifica to produce microcystins in Iraqi freshwaters via using molecular and immunological tools. The toxigenicity of W. prolifica was compared via laboratory experiments with other dominant bloom-forming cyanobacteria isolated from the Tigris River: Microcystis aeruginosa, Chroococcus turigidus, Nostoc carneum, and Lyngbya sp. significant expression of mcyE gene and microcystin production was most evident in W. prolifica. Contrary to the prevailing concept that M. aeruginosa is a main microcystin producer in freshwaters around the world, no significant microcystin production was observed with this species throughout the time points studied in our laboratory methods. As for C. turigidus, N. carneum and Lyngbya sp., neither mcyE expression nor microcystin production was significant. Data from mcyE expression by RT-qPCR were generally in agreement with those obtained from microcystin quantification by ELISA. Interestingly, W. prolifica, which showed clear microcystin-producing ability in this study and which was not reported before in the literature to produce microcystin, can be added as a new microcystin producer to the list of toxigenic cyanobacteria.